1961
DOI: 10.1515/bchm2.1961.325.1.283
|View full text |Cite
|
Sign up to set email alerts
|

Die Konstitution des normalen adulten Humanhämoglobins

Abstract: Hämoglobine bestehen aus zwei Komponenten: dem eisenhaltigen Häm lind Protein (Globin). Das Mol.-Gew. wurde in der Ultrazentrifuge zu 66-68000 ermittelt 1 . Auf dieses Mol.-Gew. bezogen, besteht die Partikel aus vier Fe-Atomen, vier Porphyrinringen und vier Peptidketten, von denen je zwei identisch vorliegen 2 . Die vier Harne sind für alle Ketten identisch. Die Konstitution dieses Anteils wurde von Hans Fischer ermittelt.Im folgenden wird über die vollständige chemische Struktur des Proteins der Hauptkomponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0
2

Year Published

1963
1963
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(53 citation statements)
references
References 2 publications
3
48
0
2
Order By: Relevance
“…In this context, adult mammals (Braunitzer et al, 1961;Leclercq et al, 1981) and birds (Rücknagel et al, 1984;Oberthür et al, 1983;Oberthür et al, 1986) have been reported to have one kind of β-globin, but adult frogs (Knöchel et al, 1983;Patient et al, 1983) contained two subtypes of β-globin chains. Due to an inconsistency in the number of subtypes of adult β-type globin-chains among amphibians, reptiles, birds and mammals, reinvestigations are needed, especially, in regards to the evolution of Tetrapoda (Benton, 1990;Hardison, 1998).…”
Section: Sequence Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, adult mammals (Braunitzer et al, 1961;Leclercq et al, 1981) and birds (Rücknagel et al, 1984;Oberthür et al, 1983;Oberthür et al, 1986) have been reported to have one kind of β-globin, but adult frogs (Knöchel et al, 1983;Patient et al, 1983) contained two subtypes of β-globin chains. Due to an inconsistency in the number of subtypes of adult β-type globin-chains among amphibians, reptiles, birds and mammals, reinvestigations are needed, especially, in regards to the evolution of Tetrapoda (Benton, 1990;Hardison, 1998).…”
Section: Sequence Strategiesmentioning
confidence: 99%
“…giantea α-1 and α-2 (Shishikura and Takami, 2001), R. americanus (Oberthür et al, 1983), G. gullus (Knöchel et al, 1982), H. sapiens (Braunitzer et al, 1961). Embryonic α-like globins: H. sapiens ζ (Aschauer et al, 1981), G. gullus π' (Chapman et al, 1980;.…”
mentioning
confidence: 99%
“…Embryonic α-like globins: H. sapiens ζ (Aschauer et al, 1981), G. gullus π' (Chapman et al, 1980;. H. sapiens β-globin (Braunitzer et al, 1961).…”
mentioning
confidence: 99%
“…Spin-label-reactive groups in opossum hemoglobin are assigned on the basis of spin-label ESR spectra analyses, which show sensitivity to changes in the spin state and coordination state of heme, which reflects proximity to heme iron. Amino acid residuelocations are taken from the sequence dala of BrdUnitzer et al [25] for human and Stenzel et a].…”
Section: Resultsmentioning
confidence: 99%